2018
DOI: 10.1590/1807-3107bor-2018.vol32.0082
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines, cortisol, and nitric oxide as salivary biomarkers in oral lichen planus: a systematic review

Abstract: The etiopathogenesis of oral lichen planus (OLP) is still not fully elucidated, and it is believed that its development could involve a neuro-immune-endocrine profile. This systematic review investigated the relationship between cytokines, cortisol, and nitric oxide (NO) in the saliva of OLP patients. An electronic search was conducted in Pubmed/Medline, Scopus, LIVIVO, and Web of Science databases with no restriction of language to identify studies published up to December 2017. Data extraction was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 56 publications
2
57
0
10
Order By: Relevance
“…In turn, these mediators, such as IL-1b and TNF-a, may partially contribute to modulation of iNOS activity. 122 Notably, proinflammatory mediator production seems to be activated directly by LPS and/or be related to NO synthesis. 3,57 Moreover, NADPH-d staining has been found to be significantly more intense and to be present in more fibroblasts, angioblasts, and collagen fibers in inflamed pulp tissues than in normal healthy samples (in which staining is present in a small number of vascular endothelial cells and fibroblasts).…”
Section: Anmentioning
confidence: 99%
“…In turn, these mediators, such as IL-1b and TNF-a, may partially contribute to modulation of iNOS activity. 122 Notably, proinflammatory mediator production seems to be activated directly by LPS and/or be related to NO synthesis. 3,57 Moreover, NADPH-d staining has been found to be significantly more intense and to be present in more fibroblasts, angioblasts, and collagen fibers in inflamed pulp tissues than in normal healthy samples (in which staining is present in a small number of vascular endothelial cells and fibroblasts).…”
Section: Anmentioning
confidence: 99%
“…Salivary cortisol values have been widely studied in relation to the effects of stress- and anxiety-related psychological factors on immune diseases. Elevated salivary cortisol values have been observed in patients diagnosed with OLP than in those without this disease [ 17 , 18 , 19 ], and it has been suggested that there is a link between high cortisol levels and psychological strains as triggering factors of OLP [ 20 ]. Given reports that stress can be responsible for the recurrence of OLP, cortisol has been proposed as a possible diagnostic marker for this disease [ 21 ].…”
Section: Biomarkers In Saliva In Different Oral Diseasesmentioning
confidence: 99%
“…The role of oxidative stress in OLP has been investigated [ 113 , 114 ], and the pathogenesis of this disease has been related to nitric oxide (NO) and reactive oxygen species (ROS) [ 22 ]. Numerous studies have described higher salivary NO levels in patients with OLP than in healthy individuals [ 19 ], and elevated levels have been associated with a more severe disease progression through the production of mucosal lesions [ 22 , 23 ]. For their part, ROS have been associated with cellular oxidative stress, but there is no clear consensus on the relationship between their salivary concentrations and oxidative damage in the tissues of patients with OLP [ 22 , 24 ].…”
Section: Biomarkers In Saliva In Different Oral Diseasesmentioning
confidence: 99%
“…Otros estudios incluyen biomarcadores salivales para cáncer bucal como nitrosaminas, CD44, CD59, anticuerpos contra p53, antígeno tumoral M2BP, MRP14, profilina, histona H1, moesina, involucrina, catalasa, transferrina, "zinc finger" salival, queratina 36 y cistatina A. De manera similar, las citoquinas dependientes de NF-kB, como las inmunosupresoras IL-4, IL-10, IL-13, and IL-1RA, han sido identificadas como potenciales biomarcadores de lesiones pre neoplásicas y de cáncer bucal de células escamosas [73][74][75][76] . Además, los valores anormales en las concentraciones de los aminoácidos alanina y leucina han sido señalados como sugestivos de malignización de procesos en las glándulas parótidas por la alteración en las vías metabólicas de los cuerpos cetónicos y de los aminoácidos glucogénicos 77 .…”
Section: C) Biomarcadores Salivales Para Cáncer Bucalunclassified